(untitled) (Global Journal of Science Frontier Research, 2022)
In this article I am going to prove that the ability of all living beings to feel magnetic field is quantum in nature and all living beings feel magnetic fields through their Subconscious Proof of the relation magnet - Subconscious is the fact that when a hypnotized individual with sleeping Conscious under suggestion was seeing a tridimensional holographic image of a pigeon in his lap and was petting the pigeon when a magnet was approached to his head he said that the pigeon disappeared If so we can expect the abilities of all living beings to sense magnetic fields to be subconscious Since holographic tridimensional images are created with laser light our aura aura means light must be involved in the holographic imaging I investigated the aura for 40 years and I found it to be weak nonlinear electromagnetic field NEMF Being nonlinear this field can imprint information I found that this weak informational NEMF from the Subconscious rules and regulates everything in the body not with its strength but with the information it carries Since it relates to the aura light it must be Quantum in nature The quantum nature of the ability to feel magnetic field must be equally true for that 1 humans and 2 migrating birds which during the migration season were found to have changes in their retina and 3 blind mole rats that always built their nests at the southeastern end of their underground tunnels lost this ability when their eyes were surgically removed which proves that the sensing of magnetic field is light-related and therefore it is quantum in nature